2022
DOI: 10.3390/jcm11175059
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Effect of the Dose of Radiation Therapy and Extent of Lymphadenectomy in Patients Receiving Neoadjuvant Chemoradiotherapy for Esophageal Squamous Carcinoma

Abstract: Neoadjuvant chemoradiotherapy has been used for patients with locally advanced esophageal squamous cell carcinoma (ESCC). However, the optimal dose of radiation therapy and the effect of lymphadenectomy after neoadjuvant therapy on patient outcomes are uncertain. We retrospectively reviewed the data of patients who received neoadjuvant therapy followed by surgery for ESCC. Overall survival (OS), disease-free survival (DFS), and perioperative outcomes were compared between patients who received radiation doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Byiringiro et al have reported that the overall median survival of 5170 patients who underwent esophagectomy was 42 months [3]. Pai et al analyzed 126 patients with neoadjuvant chemoradiotherapy and found that 3-year overall survival (OS) is 45%~54% and disease free survival (DFS) 34%~37% [4]. Thus, new prognostic markers and therapeutic strategies are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Byiringiro et al have reported that the overall median survival of 5170 patients who underwent esophagectomy was 42 months [3]. Pai et al analyzed 126 patients with neoadjuvant chemoradiotherapy and found that 3-year overall survival (OS) is 45%~54% and disease free survival (DFS) 34%~37% [4]. Thus, new prognostic markers and therapeutic strategies are urgently needed.…”
Section: Introductionmentioning
confidence: 99%